Comportamento elástico da madeira laminada colada cruzada de dormentes reaproveitados - Vinnicius Dordenoni Pizzol (2018)
The thesis aims to ensure the elastic characterization of cross-laminated laminated wood made from discarded railway sleepers. Five CLT plates were prepared with previously classified and visually selected boards and by ultrasound, excitation and flexion waves (in the elastic regime), which were grouped with resorcinol-formaldehyde adhesive with an optimum pressure, also predetermined. The plates were compressed and deformed with strain gauges in the elastic regime, determined some elastic constants, then unfolded in smaller samples with the orientation defined in six directions: the three main, 3 longitudinal layers (3L) , 2 longitudinal layers (2L) and regular (R) layers; and the three intermediates, 3L, 2L (45 °), 3L, R (45 °) and 2L, R (45°) were used to determine all elastic properties in the compression test (deformations measured by displacement meters) and waves of excitation, the latter at room temperature and at high temperatures, thus analyzing the viability of the method and, so as to explain the behavior at high temperatures, the thermogravimetric test of the adhesive was carried out. The results were conclusive to: a) Evaluate positively the effectiveness of the two non-destructive tests in the classification of the boards (slides); b) Determine all the elastic constants and, consequently, the flexibility matrix and finally; c) Define that the adhesive influenced more than the wood in high temperatures.